TDP-43 Is Elevated in Plasma Neuronal-Derived Exosomes of Patients With Alzheimer’s Disease - Zhang, Nan; Gu, Dongmei; Meng, Meng; Gordon, Marc L. (Frontiers in Aging Neuroscience, 2020)
Background: Recently, TDP-43 has been recognized as a common proteinopathy in the “oldest old” and a neuropathological comorbidity in patients with Alzheimer’s disease (AD). However, since it has a low concentration in cerebrospinal fluid, the presence of TDP-43 in AD is rarely investigated in vivo. Methods: Twenty-four patients with amyloid PET confirmed AD and 15 healthy controls (HCs) were included in this study. TDP-43 level in plasma neuronal-derived exosomes (NDEs) was measured by enzyme-linked immunosorbent assay. Results: TDP-43 level was elevated in patients with AD compared with HCs (1.20 ± 0.91 ng/ml vs 0.64 ± 0.20 ng/ml, P < 0.039), after controlling for age. There was no correlation between TDP-43 level and cognitive function, neuropsychiatric symptoms or APOE genotype in patients with AD. Conclusions: This study demonstrated increased TDP-43 accumulation in AD patients by examining plasma NDEs, which may provide a window into the effects of TDP-43 on AD progression.